Little Cloud - Carle, Eric (London Penguin Books Ltd, 2003)
A sweet, playful story in which Little Cloud loves changing shape. He can be a horse, or a tree, or even a clown. At the end of the story he joins all the other clouds in the sky to make one big cloud - and then it rains!
English stories
2
Keywords: English stories